Exploring Sarcasm In Different Movie Genres: A Case Study Of Horror And Comedy Movies - Argatha Samuel Riandika; Pasaribu, Arsen Nahum; Sembiring, Rony Arahta (English Lecturers and Teachers Association (ELTA), 2025)
This study explored how sarcasm was used in two contrasting movie genres, horror, and comedy, to understand its role in shaping tone, storytelling, and audience engagement. Drawing on Camp’s theory, sarcasm is categorized into four types: propositional sarcasm, lexical, like-prefixed, and illocutionary sarcasm. The research uses a qualitative approach, analyzing selected films and their script to identify and classify 127 sarcastic utterances—66 in horror and 61 in comedy. The findings reveal that illocutionary sarcasm is the most common in horror (50.00%), complementing the genre’s subtle and dark undertones. In comedy, propositional sarcasm takes the lead (37.70%), reflecting its playful and straightforward humor. Like-prefixed sarcasm appears the least in both genres, with 4.55% in horror and 3.28% in comedy. These results highlight how sarcasm adapts to each genre’s narrative style and audience expectations. By shedding light on the contextual differences in sarcasm’s use, this study offers valuable insights into genre-specific communication and helps deepen our understanding of sarcasm as a powerful linguistic tool in both entertainment and education. Keywords : Sarcasm; Pragmatic; Movies; Camp’s theory